An investigation into the functionalization of poly(styrene-co-maleic anhydride) with calixarenes and their potential applications - Eghbali Dogaheh, Seyed Babak (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.